A doença mental e a reforma psiquiátrica representadas por profissionais de saúde - Silva, Giselli Lucy Souza (2014)
The stigmatized view of the crazy/mentally sick prevailed over time and led to social exclusion of these individuals, making them live on the margins of society dictates normal. Currently, in an attempt to reverse this, a new proposal for attention on these social subjects, which aims to provide a more humane and targeted treatment for inclusion emerges through extra-hospital care devices implemented with the advent of the Psychiatric Reform. It is against this new social reality promoted by the psychiatric reform that this work was developed with the purpose of knowing and analyzing the representational content of mental health professionals about the crazy/mentally disease and of the Psychiatric Reform. Are two descriptive studies, qualitative in psychiatric institutions and CAPS in the cities of Campina Grande and João Pessoa. In the empirical part of this dissertation, the Study 1 aimed to identify the structure of social representations about the crazy/mentally disease and psychiatric reform in order to describe and analyze the elements of the core and peripheral system constituents of these representations, included a sample of 100 professionals in the mental health system and the instruments used were: sociodemographic questionnaire and analyzed by descriptive statistical and technique of free association words, with the stimulus: disease mental, crazy and psychiatric reform, analyzed from EVOC software. Study 2, had purpose to understand and analyze the social representations made by mental health professionals about the crazy/mentally disease and psychiatric reform through semi-structured interview and the conjugate method analysis by ALCESTE software and a thematic content analysis. Study 2 involved with a sample of 38 mental health professionals. In both studies, the instruments were applied in the work of the professional environment, individually and with the help of writer, having all needed ethical care when performed research with humans. The results show a representation still stigmatized by users of mental health services, anchored mainly by social disability. The crazy/mentally disease is recognized as someone who experiences intense suffering, victim of prejudice and requires care and treatment. According to the professionals, the psychiatric reform and deployment of substitute services have not yet been able to change the social reality of these people, and although the Reformation is represented as a change, an improvement in the treatment offered, are the faults new mental health policy which leads, in some cases, in a positioning opposed to reform since the psychiatric hospitals are still designed as required by some professionals.